2004
DOI: 10.1023/b:neab.0000036016.65208.27
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Substance P After Central Administration on the Activity of the Mesolimbic System of the Rat Brain as Studied by Microdialysis

Abstract: In vivo microdialysis was used to study the effects of substance P on dopamine, dihydroxyphenylacetic acid, and homovanillic acid levels in the nucleus accumbens in rats. Each animal received sequential injections of physiological saline, 0.1 microg of substance P, and 1 microg of substance P into the lateral ventricle over three days. Dialysates showed increases in dopamine levels in response to neuropeptide, by 41% for the 0.1 microg dose and 71% for the 1 microg dose. The dynamics of these changes also depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Substance P in limbic and extrapyramidal structures has been associated with biochemical and behavioral changes when injected into the VTA (Kelley et al 1979; Elliott et al 1986; Cador et al 1989; West and Michael 1991; Kelley and Delfs 1991; Zhou and Nyberg 2002), prefrontal cortex (Krasnova et al 2000), nucleus accumbens (Iversen 1982; Kalivas and Miller 1984; Huston and Hasenohrl 1995; Schildein et al 1998; Nikolaev et al 2004), and substantia nigra (Tan and Tsou 1988a,b). There is also evidence that SP plays a central role in mediating the abstinence reaction to psychoactive drugs such as opioids (Tiong et al 1992; Kreeger and Larson 1996; Murtra et al 2000) and antidepressants (Jones and Olpe 1984).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Substance P in limbic and extrapyramidal structures has been associated with biochemical and behavioral changes when injected into the VTA (Kelley et al 1979; Elliott et al 1986; Cador et al 1989; West and Michael 1991; Kelley and Delfs 1991; Zhou and Nyberg 2002), prefrontal cortex (Krasnova et al 2000), nucleus accumbens (Iversen 1982; Kalivas and Miller 1984; Huston and Hasenohrl 1995; Schildein et al 1998; Nikolaev et al 2004), and substantia nigra (Tan and Tsou 1988a,b). There is also evidence that SP plays a central role in mediating the abstinence reaction to psychoactive drugs such as opioids (Tiong et al 1992; Kreeger and Larson 1996; Murtra et al 2000) and antidepressants (Jones and Olpe 1984).…”
Section: Discussionmentioning
confidence: 99%
“…This type of interaction between SP and central dopaminergic systems is proposed to play an important role in mediating behavior under basal ganglia dopamine regulation (James and Starr 1979; Kelley and Iversen 1979). In addition, because the injection of this tachykinin into the VTA (Cador et al 1989; Kelley et al 1989; Kelley and Delfs 1991; West and Michael 1991), frontal cortex (Krasnova et al 2000), nucleus accumbens (Kalivas and Miller 1984; Nikolaev et al 2004), striatum (Tang et al 1998; Preston et al 2000; Krasnova et al 2000), or substantia nigra (Tan and Tsou 1988a,b) increases neuronal firing and dopamine turnover, it is not surprising that drugs which alter dopamine activity associated with these systems would also influence associated SP pathways. In fact, previous studies demonstrated that changes in activity of the dopaminergic pathways induced by amphetamines (Ritter et al 1984, 1985; Sonsalla et al 1984, 1986; Hanson et al 1986a,b, 2002; Bannon et al 1987; Ujike et al 1988) or cocaine (Alburges et al 2000; Kraft et al 2001) significantly alter SP systems in limbic and basal ganglia regions.…”
Section: Introductionmentioning
confidence: 99%
“…It is manifested in decreased neuronal density and volume (morphological signs) and in behavioral phenomena attesting to hypofunction of the brain dopaminergic system (reduction of hypothalamus self-stimulation, rotating behavior, exploratory behavior in the open field) [5][6][7]. In vivo measurements of dopamine release and metabolism in rats by the method of microdialysis demonstrated a progressive decrease in dopamine release in the nucleus accumbens in chronically alcoholized rats in parallel with deceleration of dopamine turnover [9]. All that supports the concept of predominant vulnerability of the dopaminergic system during chronic alcoholization.…”
Section: Resultsmentioning
confidence: 99%
“…One key neuropeptide released in the VTA is the tachykinin‐derived peptide substance P (SP), which is contained in a number of afferent projections to the VTA, most notably in inputs arising from the habenula and from the nucleus accumbens (Cuello et al 1978; Lu et al 1998). Microinjections of SP into the VTA increase DA in the nucleus accubmens (Deutch et al 1985; Nikolaev et al 2004), and electrophysiological studies have demonstrated that SP excites neurons in both the VTA as well as in the neighbouring substantia nigra pars compacta (Overton et al 1992; Seabrook et al 1995; Korotkova et al 2006). Consistent with these studies, intra‐VTA SP increases locomotion (Stinus et al 1978), which can be blocked by DA receptor antagonists in the nucleus accumbens (Kelley et al 1979).…”
Section: Introductionmentioning
confidence: 99%